Measurement of the ZZ Production Cross Section and Limits on Anomalous Neutral Triple Gauge Couplings in Proton-Proton Collisions at √s = 7 TeV with the ATLAS Detector - Anduaga, Xabier Sebastián (2012)
A measurement of the ⁢ production cross section in proton-proton collisions at √ =7  TeV using data corresponding to an integrated luminosity of 1.02  fb−1 recorded by the ATLAS experiment at the LHC is presented. Twelve events containing two boson candidates decaying to electrons and/or muons are observed, with an expected background of 0.3 ±0.3⁢(stat)+0.4−0.3⁢(syst) events. The cross section measured in a phase-space region with good detector acceptance and for dilepton masses within the range 66 to 116 GeV is fid⁢→ℓ+⁢ℓ−⁢ℓ+⁢ℓ− =19.4+6.3−5.2⁢(stat)+0.9−0.7⁢(syst) ±0.7⁢(lumi)  fb. The resulting total cross section for on-shell ⁢ production, tot⁢ =8.5+2.7−2.3⁢(stat)+0.4−0.3⁢(syst) ±0.3⁢(lumi)  pb, is consistent with the standard model expectation of 6.5+0.3−0.2  pb calculated at the next-to-leading order in QCD. Limits on anomalous neutral triple gauge boson couplings are derived.